Validation of some species- and genus-group names in Melitta (Hymenoptera: Melittidae) - Michez, Denis; Kuhlmann, Michael; Dellicour, Simon (Journal of Melittology, 2014)
Four recently proposed names in the genus Melitta Kirby (Melittidae: Melittinae) were left as nomenclaturally unavailable owing to minor conflicts with the recently established criteria for electronic publication.  These oversights are here corrected, thereby validating the following new names: Melitta (Afromelitta) Michez & Kuhlmann, new subgenus; Melitta (Afromelitta) richtersveldensis Michez & Kuhlmann, new species; Melitta (Plesiomelitta) Michez & Kuhlmann, new subgenus; and M. (Plesiomelitta) avontuurensis Michez & Kuhlmann, new species.